Captive Insurance Companies: Tax Shelter or Risk Solution? - Bevvino, Frank (142DTR J-1, 2016)
Keywords: dept.acc; peer-reviewed

Initial Evidence on the Association between Local Government Fiscal Distress and Environmental Protection Programs - Phillips, Janet F.; Strickland, Pamela J. (Issues in Social & Environmental Accounting, 2016)
The purpose of this study is to explore the commitment of local governments to environmental programs when fiscal distress is predicted. We hypothesize that commitment to environmental programs diminishes when the local government is experiencing fiscal distress. The regression model results indicate that local governments with high levels of debt were less likely to I mplement environmental programs and that a larger population and higher revenue are factors directly related to the commitment of local government to environmental programs. Communities that are more populous and less fiscally stressed are more likely to benefit from a local government that implements and sustains environmental programs. These results have implications for the stakeholders of local communities and broader implications for the global effort toward environmental protection and sustainable communities.
Keywords: ENVIRONMENTAL protectionSTAKEHOLDERSENVIRONMENTAL qualityENVIRONMENTAL sciencesLOCAL government finance; dept.acc; peer-reviewed

The role of non-governmental organizations (NGOs) as intermediaries of the European union decision to adopt international accounting standards: 1973-2002 - Kaya, D.; Kirsch, R.J.; Henselmann, K. (Accounting Historians Journal, 2016)
This paper analyzes the role of non-governmental organizations (NGOs) as intermediaries in encouraging the European Union (EU) to adopt International Accounting Standards (IAS). Our analysis begins with the 1973 founding of the International Accounting Standards Committee (IASC), and ends with 2002 when the binding EU regulation was approved. We document the many pathways of interaction between European supranational, governmental bodies and the IASC/IASB, as well as important regional NGOs, such as the Union Européenne des Experts Comptables, Économiques et Financiers (UEC), the Groupe d’Etudes des Experts Comptables de la Communauté Économique Européenne (Groupe d’Etudes), and their successor, the Fédération des Experts Comptables Européens (FEE). This study investigates, through personal interviews of key individuals involved in making the history of the organizations studied, and an extensive set of primary sources, how NGOs filled key roles in the process of harmonization of international accounting standards. © 2016, American Accounting Association. All rights reserved.
6 citations (Crossref) [2023-10-31]
Keywords: dept.acc